Hubungan Karakteristik dan Perilaku Ibu dalam Pemberian MP-ASI dengan Kejadian Gerakan Tutup Mulut (GTM) serta Status Gizi Bayi Usia 12-24 Bulan - Hafiza , Haura; Wani , Afivah Putri; Fitri , Aida; Sihombing , Esmina; Hutajulu , Dwi Elalia Br; Nababan, Tiarnida (Journal of Pharmaceutical and Sciences, 2025)
According to WHO 2022 data, approximately 45 million toddlers worldwide experience wasting, with malnutrition being a major contributor to child mortality. One contributing factor is suboptimal complementary feeding practices. Food Refusal Behavior (FRB), characterized by a child's mouth-closing and eating refusal, is a common phenomenon during complementary feeding that may affect nutritional status. This quantitative cross-sectional study was conducted at Hj Hanum Clinic with 43 respondents selected through total sampling to analyze the relationship between maternal characteristics/behaviors and the incidence of FRB and nutritional status in infants aged 12-24 months. Data were collected through questionnaires and observations, then analyzed using chi-square tests. Results revealed significant associations between FRB incidence and parity (p<0.001), maternal behavior (p<0.001), and maternal occupation (p=0.002). Similarly, child nutritional status showed significant relationships with these three factors. However, maternal education demonstrated no significant association with either FRB incidence (p=0.539) or child nutritional status (p=0.149). These findings underscore the importance of considering parity and maternal behavior in FRB prevention and nutritional status improvement, while formal maternal education appears non-determinative in this context.